PhotoVideoPhone Mastery Class 2018 / Dian Aszyanti Atirah Mohd Asri and Suria Sulaiman - Mohd Asri, Dian Aszyanti Atirah; Sulaiman, Suria (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
The PhotoVideoPhone Mastery Class 2018 was held on September 15th, 2018. It was successfully organized by MASMED for Faculty of Hotel and Tourism Management's student through UiTM entrepreneurship funds. A total of 35 UiTM students and staff were involved in the course. This PhotoVideoPhone Mastery course had invited a professional photographer Ms Kamalia Kamal or famously known as 'Kak Kay' from a popular photography company named 'The Photolicious'. The course aimed to provide insights and creative techniques to produce quality photos for online business promotion. During the sharing session, Kak Kay was very happy to share her knowledge and exposed the participants to photo and video concept and techniques for more effective business strategy. She also encouraged and motivated the young entrepreneurs not to give-up in doing business. She also expects more entrepreneurs to use the PhotoVideoPhone techniques to help them in business. This practical course was easily understood. Participants were very satisfied with the knowledge and experiences shared by Kak Kay. Hopefully the course conducted can be fully utilized by the participants.